Is There Student Anxiety in Physical Education Learning during the COVID-19 Pandemic in Indonesia? - Erick Burhaein (JUMORA: Jurnal Moderasi Olahraga, 2022)
Anxiety as one of the psychological aspects may have an influence on physical education learning (penjas) during the COVID-19 pandemic. The purpose of this article is to find out about students' anxiety in tailor learning during the COVID-19 pandemic. The method used in writing this article is literature studies. Methods used in article search and making research inquiries to uncover new findings using the PICO method. Access used by authors using google scholar in the form of nationally accredited articles with a range of issues march 2020 to October 2021. The data collection technique using the PRISMA method from a total of 52 reference sources from the google schoolar database is then filtered to get 4 references in the final stage that will be a literature review. The results of the library study showed that there was student anxiety in physical education learning during the COVID-19 pandemic in Indonesia. The findings of 50% of the studies that self-reviewed showed there was a level of student anxiety in the category is sufficient. The remaining 50% of the studies self-reviewed showed there were high levels of student anxiety in the high categories. This review literature study has implications for the known anxiety condition of students in learning during the COVID-19 pandemic in Indonesia. These findings contribute as material for further study for the creation of appropriate learning methods to address student anxiety in tailor learning during the COVID-19 pandemic. Optimization through the right methods will also optimize the benefits of tailors to improve health during pandemics. Keywords: anxiety, COVID-19, pandemic, physical education, students